Serum cytokine and chemokine profiles and disease prognosis in hepatitis B virus-related acute-on-chronic liver failure - Zhu, Bingbing; Gao, Fangyuan; Li, Yuxin; Shi, Ke; Hou, Yixin; Chen, Jialiang; Zhang, Qun; Wang, Xianbo (Frontiers in Immunology, 2023)
Background: Hepatitis B virus-related acute-on-chronic liver failure (HBV-ACLF) has significant morbidity and mortality and is associated with the induction of cytokines/chemokines, which might contribute to the pathogenesis of liver injury. This study aims to explore the cytokines/chemokines profiles of HBV-ACLF patients and develop a composite clinical prognostic model. Methods: We prospectively collected blood samples and clinical data of 107 HBV-ACLF patients admitted to the Beijing Ditan Hospital. The concentration of 40-plex cytokines/chemokines were measured by the Luminex assay in 86 survivors and 21 non-survivors. Discrimination between cytokine/chemokine profiles in different prognosis groups were analyzed using the multivariate statistical technique of principal component analysis (PCA) and partial least square discriminant analysis (PLS-DA). The immune-clinical prognostic model was obtained using multivariate logistic regression analysis. Results: The PCA and PLS-DA method indicated that the cytokine/chemokine profiling could distinguish patients with different prognosis clearly. 14 cytokines including IL-1β, IL-6, IL-8, IL-10, TNF-α, IFN-γ, CXCL1, CXCL2, CXCL9, CXCL13, CX3CL1, GM-SCF, CCL21 and CCL23 were significantly correlated with disease prognosis. Multivariate analysis identified CXCL2, IL-8, total bilirubin, and age as independent risk factors that constituted the immune-clinical prognostic model, which showed the strongest predictive value of 0.938 compared with the CLIF-C ACLFs (0.785), MELD (0.669), and MELD-Na (0.723) (P < 0.05 for all). Conclusions: Serum cytokine/chemokine profiles correlated with 90-day prognosis of patients with HBV-ACLF. The composite immune-clinical prognostic model we proposed resulted in more accurate prognostic estimates than CLIF-C ACLFs, MELD, and MELD-Na.